Jeju Island: Reaching to the Core of Beauty (Korea Essentials, 2011)
Korea's largest island, Jeju forms a roughly oval shape stretching 75 kilometers from east to west and 41kilometers, at its widest, from north to south. It is located off the southernmost coast of Korea, lying between China and Japan. The four seasons are distinct, though the climate is mild. The temperature rarely falls below freezing in winter, except at the summit of Mt. Halla. Now the recipient of UNESCO designation in three categories of natural science, and a finalist in the international New 7 Wonders of Nature campaign, Jeju is also renowned for its ecology. Forged by volcanic activity,